Visitor Experience on Visitor Management Practices in Wildlife Tourism Destinations (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Wildlife tourism is one of the important  components of tourism around the world.  Kerala, better known as “God’s own Country”  which is a federal state of India is one of the  sought after tourism destinations for tourists  across the world. Wildlife tourism is the  upcoming sector of tourism development as  far as Kerala tourism is concerned. When the  visitors get positive experience, they are likely  to revisit or recommend the destination to  others. So it is very important to identify the  factors underlying the experience of visitor  management in wildlife tourism areas. In this  paper, the researchers developed a scale to  examine the core factors contributing to the  experience of visitors on visitor management.  The study found that the factors contributing to  visitor management experiences are Experience  on Directorial Information, Experience on  Modification of the Site, Experience on  Management related Information, Experience  on Interpretive information, Experience on Site  Personnel, Experience on Ticket Counter and  Experience on Destination Vehicle.
Keywords: visitor management; visitor experience; wildlife tourism; destination